Microplankton (phyto- and bacterioplankton) during austral autumn in the coastal waters of the Argentina Islands Archipelago, Antarctica - Seregin, S. A.; Bryantseva, Yu. V.; Chmyr, V. D. (Ukrainian Antarctic Journal, 2003)
Biomass and production of the bacterio- and phytoplankton were measured in the region of the Ukrainian Antarctic station Akademik Vernadsky at the end of March, 1998. There were marked 70 taxons of planktonic algaes in the composition of the "autumnal" phytoplankton in the Argentina islands archipelago waters. Biomass dominated were Bacillariophyceae, and the first of all, Corethron criophylum. Flagellates were most abundantly at the half of stations; the diatom algaes (Chaetoceros, Corethron, Fragilariopsis) were numerous and, at some stations, Coccolitophoridаe, as well. Measured primary production in the surface waters, on the average, was 9,66 ± 6,87 mg C m-3 day-1 (from 3,0 up to 15,86), and counted primary production – 7,55 ± 2,61 mg C m-3 day-1 (from 1,14 up to 12,61). The mean number of bacterioplankton was at the level of 0,5 million cells ml-1. Contribution of bacterial production in the surface layer was, on the average, 52 % of the primary production of phytoplankton.